Performance Evaluation of a Simple, Locally-Designed Padi Thresher - Wan Ismail, Wan Ishak; Mohd Lassim, Mohammad; Mohd Hanif, Ahmad Husni (1984)
Performance evaluation studies of a padi thresher designed at Universiti Pertanian Malaysia Cawangan Sarawak indicated that it was a high capacity thresher. Using manual labour, it was capable of threshing padi at a rate of 45 to 68 kg/hr. The skill and the physical power of the operator determined the actual rate of threshing. However, when engine powered, threshing was accomplished at a constant 121.3 kg/hr. Thresing efficiency was found to be 87% or higher and product purity was 79% or higher. The possibility of this thresher being adopted for use by padi farmers is good because there is a marked increase in output per man-hour over manual threshing. In addition, it is cheap, light and easy to fabricate.